PR 2.0 and interaction of Turkish Brands in Terms of Brand Awareness - Ece BABAN (Online Academic Journal of Information Technology, 2012)
Today, under the affect of market conditions, companies prefer social media channel with the aim of reaching their target population, interacting with their customers directly and expressing their brands more powerfully in the market. Companies are trying to perform new strategies for creating close relationships between brand and customers, while the differentiation attempts of the companies. Nowadays, the Internet phenomenon is one of the most important factors in this regard. People spend most of their times at the computer and internet networks. In the 1990s, with the spread of internet and mobile phones, public relations activities moved to electronic and digital media of mass communication as a one-way by using e-mail, SMS and fax machine tools (Jalali, 2009:32). In the 2000s, by the development in web area, with the help of 2.0 patches, people can also edit the pages instead of just reading the written pages through the web pages. In today's competitive environment and the developments that followed the progress of technology companies and companies with a progressive web influenced by these developments and the opportunities created by social media, they introduce their products and services and increase customer satisfaction for better uses. PR activities which use Web 2.0 and technological developments in social media environment are called PR 2.0 (Jalali, 2009:45). Throughout the research, PR 2.0 activities within the scope of the contribution of brand awareness through social media, especially in comparison with traditional PR will be discussed. Brands will be examined regarding the brands which are actively using the social media in terms of the public relations and brand awareness. Brands can be listed in four different business sectors such as; Mavi Jeans, Anadolu Efes Pilsen, Garanti Bankası and ETI.